Effect of electroacupuncture on the repair of stress ulcer injury in neurocritical patients: A randomized clinical trial - Li, He; Li, Li-li; Wang, Jian; Wang, Yong-qiang; Wang, Lan; Yuan, Lan; Chen, Wen-ting; Song, Jian-gang (Frontiers in Medicine, 2022)
Background Stress ulcer (SU) is one of the main causes of prolonged hospital stay, poor prognosis, and increased mortality in critically ill patients. This study aimed to investigate the effect of electroacupuncture (EA) on SU in patients with severe neurological diseases and explore its possible mechanisms. Methods Taking patients with SU in adult neurocritical care as the research object, they were randomly divided into the EA group and the control group. Through the perioperative EA intervention, the following indicators were documented: main observation indicator (the effective rate of SU treatment), secondary observation indicators (gastric juice pH, gastric juice occult blood test, and stool occult blood test), related mechanisms [repair factors trefoil factor family 2 (TFF2), vascular endothelial growth factor (VEGF), and heat shock protein 70 (HSP70)], complications during hospitalization, and intensive care unit (ICU) stay time. Results Compared with the control treatment, EA increased the effective rate of SU treatment (85.4% for the EA group, 57.5% for the control group, risk difference: 27.9% (95% CI: 8.3%–45.1%); P < 0.01). EA increased the success rate of gastric juice pH treatment on days 1, 2, and 3 (P < 0.01 for day 1, P < 0.05 for days 2 and 3). EA lowered the positive rate of gastric occult blood test on days 1 and 3 (all P-values < 0.05) and the positive rate of fecal occult blood test on day 3 (P < 0.05). EA also reduced the ICU stay time (P < 0.01) and total hospitalization time (P < 0.05). Compared with day 0, all serum repair factors (VEGF, HSP70, and TFF2) of both groups significantly increased on days 1, 3, and 5 (all P-values < 0.01). Compared with the control group, VEGF in the EA group was increased on days 3 and 5 (all P-values < 0.01); HSP70 was increased on days 1, 3, and 5 (P < 0.05 for day 1, P < 0.01 for days 3 and 5); and TFF2 was increased on days 1, 3, and 5 (all P-values < 0.01). Conclusion Electroacupuncture promoted the repair of SU damage in severe neurological disease, and its effect was related to enhancing the expression of gastric mucosal repair factors. Clinical trial registration [https://www.chictr.org.cn/showprojen.aspx?proj=127012], identifier [ChiCTR2100046701].